Association of negative financial shocks during the Great Recession with depressive symptoms and substance use in the USA: the CARDIA study. Issue 12 (11th August 2020) - Swift, Samuel Longworth; Elfassy, Tali; Bailey, Zinzi; Florez, Hermes; Feaster, Daniel J; Calonico, Sebastian; Sidney, Steve; Kiefe, Catarina I; Zeki Al Hazzouri, Adina
Abstract : Background: The Great Recession of 2008 was marked by large increases in unemployment and decreases in the household wealth of many Americans. In the 21st century, there have also been increases in depressive symptoms, alcohol use and drug use among some groups in the USA. The objective of this analysis is to evaluate the influence of negative financial shocks incurred during the Great Recession on depressive symptoms, alcohol and drug use. Methods: We employed a quasi-experimental fixed-effects design, using data from adults enrolled in the Coronary Artery Risk Development in Young Adults (CARDIA) study. Our financial shock predictors were within-person change in employment status, income and debt to asset ratio between 2005 and 2010. Our outcomes were within-person change in depressive symptoms score, alcohol use and past 30-day drug use. Results: In adjusted models, we found that becoming unemployed and experiencing a drop in income and were associated with an increase in depressive symptoms. Incurring more debts than assets was also associated with an increase in depressive symptoms and a slight decrease in daily alcohol consumption (mL). Conclusion: Our findings suggest that multiple types of financial shocks incurred during an economic recession negatively influence depressive symptoms among black and white adults in the USA, and highlight the need for future research on how economic recessions are associated with health.